An abdominal and unexpected cause of persistent fever in a 3-year old boy - Pierluigi Marzuillo; Anna Grandone; Anna Di Sessa; Tiziana Esposito; Nicoletta Della Vecchia; Carlo Capristo; Emanuele Miraglia del Giudice; Laura Perrone (Turkish Journal of Gastroenterology, 2019)
-